Wine Tourism as a Great Opportunity for Georgia - Meladze, Maia (European Scientific Journal, ESJ, 2017)
In a region with such an extensive wine history and culture, wine and food will be an important component of tourism. As more ventures get off the ground, Georgia will develop a critical mass of wine tourism offerings. Georgia’s traditional winemaking method of fermenting grapes in earthenware, egg-shaped vessels has been added to the world heritage list of UNESCO. Georgia’s ancient wine culture has seen a revival in recent years. Winemakers have realized that their traditional method of qvevri winemaking is one of their most valuable assets. In the last decade, wine tourism has become a key component of gastronomy tourism and a pillar in the strategies of diversification of many destinations. The quality, styles, and value of Georgian wine available internationally will stimulate interest in Georgian wine tourism, more so than vice versa.